2019
DOI: 10.1002/bjs.11115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resection margin status on recurrence and survival in pancreatic cancer surgery

Abstract: Background The prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) is poor and selection of patients for surgery is challenging. This study examined the impact of a positive resection margin (R1) on locoregional recurrence (LRR) and overall survival (OS); and also aimed to identified tumour characteristics and/or technical factors associated with a positive resection margin in patients with PDAC. Methods Patients scheduled for pancreatic resection for PDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
128
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(149 citation statements)
references
References 48 publications
13
128
1
7
Order By: Relevance
“…11,12 The remaining 30% present with disease that interfaces with major vascular structures, making it either borderline resectable or locally advanced (stage 3). Metastases most commonly are to lymph nodes outside standard lymphadenectomy stations, peritoneum, liver and lungs, and may be identified by CT. 13 Magnetic resonance imaging is more accurate for characterising indeterminate liver lesions. 14 Positron emission tomography (PET)/CT is increasingly being used to determine staging and may change the treatment plan for up to 20% of patients.…”
Section: Stagingmentioning
confidence: 99%
“…11,12 The remaining 30% present with disease that interfaces with major vascular structures, making it either borderline resectable or locally advanced (stage 3). Metastases most commonly are to lymph nodes outside standard lymphadenectomy stations, peritoneum, liver and lungs, and may be identified by CT. 13 Magnetic resonance imaging is more accurate for characterising indeterminate liver lesions. 14 Positron emission tomography (PET)/CT is increasingly being used to determine staging and may change the treatment plan for up to 20% of patients.…”
Section: Stagingmentioning
confidence: 99%
“…In this study, we summarize the experience of a tertiary institution in the management of patients diagnosed with a resectable pancreatic tumour and a concurrent primary extra‐pancreatic malignancy. Ten patients underwent pancreatic resections under these circumstances, with minimal morbidity, no 90‐day mortality and long‐term survival rates comparable to, or more favourable than, patients diagnosed with a pancreatic malignancy without the presence of a synchronous extra‐pancreatic tumour . Eight patients remained alive, with a median follow‐up period of 41.3 months.…”
Section: Discussionmentioning
confidence: 95%
“…Ten patients underwent pancreatic resections under these circumstances, with minimal morbidity, no 90-day mortality and long-term survival rates comparable to, or more favourable than, patients diagnosed with a pancreatic malignancy without the presence of a synchronous extra-pancreatic tumour. 19,20 Eight patients remained alive, with a median follow-up period of 41.3 months. Of these patients, six underwent pancreatic resections for a PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…We appreciate the interest of Fiorillo et al . in our study and thank them for their comments. Indeed, the results of our study showed that patients with N0 disease had significantly worse survival after R1 compared with R0 resection and comparable survival in N1 disease.…”
Section: Overall Survival By Lymph Node Status and Radicalitymentioning
confidence: 88%